2014
DOI: 10.1128/jvi.00544-14
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire of Epitopes Recognized by Serum IgG from Humans Vaccinated with Herpes Simplex Virus 2 Glycoprotein D

Abstract: ). The vaccine consisted of a soluble form of herpes simplex virus 2 (HSV-2) glycoprotein D (gD2) with adjuvant. The goal of the current study was to examine the composition of the humoral response to gD2 within a selected subset of vaccinated individuals. Serum samples from 30 vaccine recipients were selected based upon relative enzyme-linked immunosorbent assay (ELISA) titers against gD2; 10 samples had high titers, 10 had medium titers, and the remaining 10 had low ELISA titers. We employed a novel, biosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 42 publications
(51 reference statements)
1
55
0
Order By: Relevance
“…A recent vaccine trial using gD as the sole immunogen failed to protect doubly seronegative women against genital HSV-2 disease but did show some efficacy against HSV-1 (7,32,33). In 10 samples with the most potent neutralizing activity, we found that the strongest correlates of neutralization were the overall gD-specific IgG content, and the combined response to the four major gD epitopes (34). These data suggest that optimal virus neutralization, and possibly protection, would be achieved by strong and balanced responses to the major neutralizing epitopes of gD.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…A recent vaccine trial using gD as the sole immunogen failed to protect doubly seronegative women against genital HSV-2 disease but did show some efficacy against HSV-1 (7,32,33). In 10 samples with the most potent neutralizing activity, we found that the strongest correlates of neutralization were the overall gD-specific IgG content, and the combined response to the four major gD epitopes (34). These data suggest that optimal virus neutralization, and possibly protection, would be achieved by strong and balanced responses to the major neutralizing epitopes of gD.…”
mentioning
confidence: 68%
“…We also included the non-neutralizing MAb MC14, which significantly enhances neutralization by MAb MC2 (36). In two previous studies of either gD-vaccinated subjects (34) or naturally infected people (35), IgGs from all samples blocked key conformational anti-gD epitopes (MC23, DL11, MC2, and MC5), and yet none blocked binding to linear epitopes (1D3 and MC14). In the present study, all nine sera in the recurrent group blocked the binding of MC23, DL11, and MC5 above a 20% threshold (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). We used an arbitrary cutoff point of 20% in scoring samples positive for blocking (45). Surprisingly, none of the 10 IgGs blocked MAbs 1D3 or MC14 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the responses to these six gD epitopes in naturally infected individuals, we used a protein-binding competition assay using surface plasmon resonance/biosensor (8,44,45). The goal was to determine whether and to what extent the binding of these MAbs to gD is diminished by preincubation of gD with human IgG.…”
Section: Resultsmentioning
confidence: 99%